The Role of Tour Guide in Preventing Deviant Behavior of Foreign Tourists in Bali - I Gede Ngurah Primanda S Rahadiarta; Ni Luh Dea Enjelita; Ni Komang Putri Widiantari (PT FORMOSA CENDEKIA GLOBAL, 2025)
Deviant behaviour refers to actions that violate the norms, values of the local culture and society. The study employs a qualitative approach, using interviews, questionnaires, observations, and document analysis to collect data from various stakeholders, including government, tourism associations, tour guides, and foreign tourists. The study finds that tour guides play a crucial role in providing accurate information and education about the destinations and the expected behaviours of tourists. However, many foreign tourists prefer traveling without tour guides due to financial, personal, or informational reasons. The study suggests that the role of tour guides needs to be supported by other parties, such as the government, law enforcement, and the community, to ensure the quality and sustainability of tourism in Bali.